Taste education and perverse gastromanias: some reflections - Cavalieri, Rosalia (E|C, 2020)
This paper aims to draw attention to taste education, an urgently topical issue that is still largely ignored or underestimated, both by politics and by educational institutions. Although today there is a lot of talk about food, cooking, taste and more generally about nutrition, this rampant collective craving is often not matched by a real awareness, a cultural study and correct information. Proof of this is the planetary spread of pathologies related to food and the phenomena of environmental impoverishment related to the production of unsustainable food and therefore to our styles of consumption. Hence, therefore, an invitation to reflect on the need to increase our food knowledge, to promote knowledge and critical consumption. The pleasure of eating is a natural and inalienable right, to which we can and we must be educated because the quality of our life and that of the environment depend on it.